Mobile-augmented reality framework for student self-centred learning in higher learning education - Aaron frederick Bulagang (2018)
Mobile learning has contributed significantly in the field of higher learning education (HLE) in Malaysia since its emergence. Mobile learning is an educational system which uses portable or wireless devices for learning purposes. As technology evolved over the decades, mobile learning concept was introduced. It was originated and developed from e-learning. Augmented reality or well-known as AR combines real environment with virtual object that users can interact. Mobile- Augmented Reality can be applied in education with the use of mobile devices such as smartphones and tablets which support AR. Application of mobile-Augmented Reality in education helps to attract the interest of students during learning sessions. The existing problems with mobile learning application are the visualization and content presentation, which may not be appealing for students as it is mostly text-based. Moreover, the user interface of mobile learning may not be adaptable for an inexperienced user and the available frameworks for mobile- Augmented Reality is still limited. The aim of this research is to propose a framework for developing a mobile-Augmented Reality application in higher learning education to support the development for various courses offered at higher learning education in Malaysia. Thus, increasing the student motivation towards learning by using AR. The objective of this research is to develop an mAR application for Networking Fundamental course with visualization tool. The next step is to evaluate the relationships of Satisfaction, Motivation, Self-Efficacy and Features towards Effectiveness to find its significance through empirical testing. Then Designing a framework for developing an mobile-Augmented Reality application for learning. Methods that were used in this research are quantitative method using questionnaire that were distributed to the participants at five universities and analyzing the data using SPSS and SmartPLS to produce results to find significant relationship. From the result, it was found that mAR had two significant relationship between Self-Efficacy and Motivation towards Effectiveness. Which means that these are the two fields that future researchers and developers should focus to increase the learning outcome of students.